WiFi Probe Request를 이용한 유동인구 자료수집 및 분석 적용 AI 연구 - 이우익(Woo-Wick Lee); 박대우(Dea-woo Park) (한국정보통신학회논문지, 2024)
유동 인구의 흐름을 분석하면, 공공 정책, 기업전략 및 상권분석 등에 활용할 수 있다. 기존의 장치는 개인 단말기의 WiFi 신호를 감지하려고 지주, 건물 등에 설치된다. 하지만, 이러한 장치들은 실제 인도에 인접하지 않는 경우가 많고, 전원을 상시 공급하지 못하거나, 특히 강화된 개인정보보호법의 제한으로 개인 단말기 식별정보를 수집하는데 한계가 있다. 본 논문은 WiFi 스캐너로 보행자의 스마트폰에서 전파되는 WiFi Probe Request 신호를 정확하게 수집하도록 설계한다. 또한 개인정보보호법에 위반되지 않는 스마트폰 네트워크 MAC 정보를 클라우드 서버로 전송하는 중계기 대한 연구를 한다. 또한 태양광과 압전 발전을 이용한 자가발전 시스템으로 기존 통신전송기 전원 문제를 해결한다. 본 논문에서 WiFi Probe Request를 이용한 유동 인구 분석을 위한 학습 데이터의 수집과 인공지능 분석 기술을 설계한다. 본 논문의 결과는 상권분석, 기업전략, 공공 정책에 활용되며, 무선통신과 인공지능 기술 발전에 기여할 것이다. Analyzing the flow of crowd counting can be used for public policy, corporate strategy, and commercial district analysis. Existing devices are installed on poles, buildings, etc. to detect WiFi signals from personal devices. However, these devices are often not located adjacent to actual sidewalks, do not provide power at all times, or have limitations in collecting personal terminal identification information, especially due to restrictions under the strengthened Personal Information Protection Act. This paper designs a WiFi scanner to accurately collect WiFi. We also conduct research on a repeater that transmits smartphone MAC information to a cloud server that does not violate the Personal Information Protection Act. In addition, it solves the power problem of existing communication transmitters with a self-generating system using solar power and piezoelectric power generation. The results of this paper will be used in commercial analysis, corporate strategy, and public policy, and will contribute to the development of wireless communication and artificial intelligence technology. KCI Citation Count: 0